Automatic Synthesis of Regular Expressions from Examples. - Bartoli, Alberto; Davanzo, Giorgio; De Lorenzo, Andrea; Medvet, Eric; Sorio, Enrico (Computer (00189162), 2014)
A system that can produce regular expressions from user-provided examples performed with high precision and recall in 12 text-extraction tasks from real-world datasets, demonstrating the effectiveness of text extraction based on genetic programming.